2011
DOI: 10.1124/jpet.111.179606
|View full text |Cite
|
Sign up to set email alerts
|

Toward Selective Drug Development for the Human 5-Hydroxytryptamine 1E Receptor: A Comparison of 5-Hydroxytryptamine 1E and 1F Receptor Structure-Affinity Relationships

Abstract: The 5-hydroxytryptamine (5-HT) 1E receptor is highly expressed in the human frontal cortex and hippocampus, and this distribution suggests the function of 5-HT 1E receptors might be linked to memory. To test this hypothesis, behavioral experiments are needed. Because rats and mice lack a 5-HT 1E receptor gene, knockout strategies cannot be used to elucidate this receptor's functions. Thus, selective pharmacological tools must be developed. The tryptamine-related agonist BRL54443 [5-hydroxy-3-(1-methylpiperidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…We bought some of the compounds in another chemical form to confirm this hypothesis. For instance, compound 3E8 in the library, BRL 54443, a 5-hydroxytryptamine receptor 5-HT 1e & 5-HT 1F agonist [32], showed no activity alone in our assay (Fig. 6B) whereas maleic acid confirmed its activity and showed an EC 50 = 93.8 AE 1.3 mM and E max = 32.6 AE 3% when assayed in the presence of FSK.…”
Section: Secondary Screening Of the Selected Hitssupporting
confidence: 72%
“…We bought some of the compounds in another chemical form to confirm this hypothesis. For instance, compound 3E8 in the library, BRL 54443, a 5-hydroxytryptamine receptor 5-HT 1e & 5-HT 1F agonist [32], showed no activity alone in our assay (Fig. 6B) whereas maleic acid confirmed its activity and showed an EC 50 = 93.8 AE 1.3 mM and E max = 32.6 AE 3% when assayed in the presence of FSK.…”
Section: Secondary Screening Of the Selected Hitssupporting
confidence: 72%
“…On the other hand, a postmortem study of untreated suicidal victims with a confirmed history of depression showed a much higher density of 5-HT 1D receptors in the globus pallidus [138]. The observed high expression of the 5-HT 1E receptor in the frontal cortex and hippocampus may indicate the relationship between 5-HT 1E receptors and cognitive functions and memory [20,139].…”
Section: The 5-ht 1d 5-ht 1e and 5-ht 1f Receptorsmentioning
confidence: 97%
“…The 5‐ht 1E receptor has also never been shown to be functionally linked to a second messenger system in animal tissue; 5‐ht 1E receptors have only been shown to couple to G i/o signalling pathways in recombinant cell lines (Adham et al ., 1994; Klein et al ., 2011). BRL54443 is the only drug known to be partly selective for the 5‐ht 1E receptor; it is also equipotent at 5‐HT 1F receptors (Brown et al ., 1998).…”
Section: Introductionmentioning
confidence: 99%